The Outcomes of Occlusive vs Non-Occlusive Culprit Coronary Artery in Non-ST-Segment Elevation Acute Coronary Syndrome (NSTEACS): A Descriptive Prospective Study in a Tertiary Cardiac Centre in Sudan - Mohamed, Dr Awad; Alamein, Mawia; Gammer, Fatma; Elmakki, Ehab; Hamid, Dr Eltayeb; Gadour, Dr Eyad; Abdelhameed, Dr Mohamed; Alamean, Dr Mohammed Ibrahim; Subahi, Professor Saad (International Journal of Innovative Research in Medical Science, 2023)
Background: Non-ST-segment elevation acute coronary syndrome (NSTEACS) is a common presentation of acute coronary syndrome. Revascularization as treatment for Acute Coronary syndrome in the republic of Sudan is free to all comers whether STEMI of NSTEMI. Urgent revascularization within the 24hrs mark, however, is only offered to patients with STEMI, as the ST segment elevation in the presenting ECG is believed to indicate an occluded culprit coronary artery and hence, the urgency to open the occluded culprit artery. This puts patients with NSTEMI categorically in a different lower risk stratum in terms of urgency for treatment. The frequency and outcomes of NSTEMI patients with occluded culprit coronary artery despite absence of ECG ST elevation in Africa, as general, are yet to be fully elucidated. Objectives: This prospective single study aimed to investigate the frequency and outcomes of NSTEMI (No ST segment elevation) Sudanese patients proven to have an occluded culprit coronary artery (TIMI flow 0). Methods: In this prospective single-center study, 100 NSTEACS conductive patients who were admitted to Al-Shaab Teaching Hospital Khartoum- Sudan from January to April 2022 were examined. Data regarding demographics, medical history, clinical presentations, laboratory investigation, electrocardiography (ECG) findings, echocardiogram, coronary angiography (CAG), management strategies, medications at discharge and follow up, 30-day outcomes, and 6-month mortality rates were collected. All patients underwent standard medical management and CAG within 24-48 hours of admission. Results: In total, 100 consecutive patients with NSTEACS were enrolled in this study, with 20% (n = 20) having occluded culprit artery (OCA) and 80% (n = 80) have no occluded culprit artery (non-OCA). Patients with OCA were younger (mean age 57.6 ± 10.7 years vs. 64.3 ± 11.1 years, p = 0.002) and predominantly male (70% vs. 48.8%, p = 0.06) as compared to those with non-OCA. Patients with OCA had a higher percentage of major cardiovascular risk factors (diabetes, hyperlipidemia, and smoking) than patients with non-OCA, except for hypertension, which was higher among patients with non-OCA (70% vs. 45%, p = 0.045). At admission, patients with OCA had a higher percentage of heart failure (20% vs. 7.5%, p = 0.05) and a lower ejection fraction (mean EF% 49.5 ± 13.7 vs. 54.3 ± 9.5, p = 0.04) as compared to patients with non-OCA. T-wave inversion was the most common ECG finding in both groups. With regard to the culprit coronary artery, the right coronary artery (RCA) was the most frequently involved in NSTEACS patients with OCA (60%), followed by the left circumflex artery (LCX) (20%), left anterior descending artery (LAD) (15%), and obtuse marginal artery (5%). In contrast, the LAD was the most involved vessel in NSTEACS patients with non-OCA (72%), followed by the RCA (49%) and the LCX (34%). The 30-day outcomes showed that the incidence of re-infarction, recurrent chest pain, and arrhythmias was higher among patients with OCA than those with non-OCA (15% vs. 5%, 25% vs. 11.3%, and 10% vs. 2.5%, respectively). However, no significant difference was noted in terms of the incidence of heart failure or death between the two groups. At 6-month follow-up, the mortality rate was noted to be higher in patients with OCA than in those with non-OCA (15% vs. 3.8%, p = 0.05). Conclusion: In this study, we can conclude that NSTEMI, in a considerable number of patients is the result of total occlusion of the culprit artery without showing ST elevation in the presenting ECG. These patients have a higher prevalence of major cardiovascular risk factors, worse clinical presentations, and worse outcomes than those with non-OCA. The RCA was the most frequently involved vessel in NSTEACS patients with OCA, while the LAD was the most involved vessel in those with non-OCA.